Effects of gamma irradiation on the biomechanical properties of peroneus tendons - Aguila CM; Delcroix GJ; Kaimrajh DN; Milne EL; Temple HT; Latta LL (Dove Medical Press, 2016)
Christopher M Aguila,1 Gaëtan J-R Delcroix,2–5 David N Kaimrajh,6 Edward L Milne,6 H Thomas Temple,5,7 Loren L Latta2,6 1Department of Biological Sciences, Florida International University, Miami, FL, USA; 2Department of Orthopaedics, Miller School of Medicine, University of Miami, Miami, FL, USA; 3Research Service & Geriatric Research, Education, and Clinical Center, Bruce W. Carter Veterans Affairs Medical Center, Miami, FL, USA; 4Interdisciplinary Stem Cell Institute, University of Miami, Miami, FL, USA; 5Vivex Biomedical Inc., Marietta, GA, USA; 6Max Biedermann Institute for Biomechanics, Miami Beach, FL, USA; 7Translational Research and Economic Development, Nova Southeastern University, Fort-Lauderdale, FL, USA Purpose: This study was designed to investigate the biomechanical properties of nonirradiated (NI) and irradiated (IR) peroneus tendons to determine if they would be suitable allografts, in regards to biomechanical properties, for anterior cruciate ligament reconstruction after a dose of 1.5–2.5 Mrad.Methods: Seven pairs of peroneus longus (PL) and ten pairs of peroneus brevis (PB) tendons were procured from human cadavers. The diameter of each allograft was measured. The left side of each allograft was IR at 1.5–2.5 Mrad, whereas the right side was kept aseptic and NI. The allografts were thawed, kept wet with saline, and attached in a single-strand fashion to custom freeze grips using liquid nitrogen. A preload of 10 N was then applied and, after it had reached steady state, the allografts were pulled at 4 cm/sec. The parameters recorded were the displacement and force.Results: The elongation at the peak load was 10.3±2.3 mm for the PB NI side and 13.5±3.3 mm for the PB IR side. The elongation at the peak load was 17.4±5.3 mm for the PL NI side and 16.3±2.0 mm for the PL IR side. For PL, the ultimate load was 2,091.6±148.7 N for NI and 2,122.8±380.0 N for IR. The ultimate load for the PB tendons was 1,485.7±209.3 N for NI and 1,318.4±296.9 N for the IR group. The ultimate stress calculations for PL were 90.3±11.3 MPa for NI and 94.8±21.0 MPa for IR. For the PB, the ultimate stress was 82.4±19.0 MPa for NI and 72.5±16.6 MPa for the IR group. The structural stiffness was 216.1±59.0 N/mm for the NI PL and 195.7±51.4 N/mm for the IR side. None of these measures were significantly different between the NI and IR groups. The structural stiffness was 232.1±45.7 N/mm for the NI PB and 161.9±74.0 N/mm for the IR side, and this was the only statistically significant difference found in this study (P=0.034).Conclusion: Our statistical comparisons found no significant differences in terms of elongation, ultimate load, or ultimate stress between IR and NI PB and PL tendons. Only the PB structural stiffness was affected by irradiation. Thus, sterilizing allografts at 1.5–2.5 Mrad of gamma irradiation does not cause major alterations in the tendons’ biomechanical properties while still providing a suitable amount of sterilization for anterior cruciate ligament reconstruction. Keywords: ACL reconstruction, allograft, sterilization, tissue banking